EXPLORING THE PREDICTIVE ROLE OF TURNOVER INTENTIONS ON EMPLOYEE TERMINATION IN HOTELS THROUGH IMPORTANT-PERFORMANCE ANALYSIS - Abdul Halim , Mohd Hafzal; Muhammad, Nur Hafizah; Mohd Nasir, Mohd Firdaus; Sehak, Muhammad Shahrim; Nasrudin, Nasmizatun Asela (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This study aims to examine the influence of self-efficacy, locus of control, and networking skills on Turnover Job Intentions among hotel employee in Malaysia. The theories used are the Theory of Planned Behavior (TPB) and Herzberg’s Two-Factor Theory as the conceptual basis. This study uses a quantitative method with a questionnaire distributed to 360 respondents which is analysed using Smart PLS-SEM to measure Important-Performance for each independent variable. The findings show that self-efficacy and locus of control have a significant positive relationship with job transfer intentions, while networking skills are not significant. Limitations of the study include a cross-sectional design that limits causal inference, data collection in Malaysia that limits generalizability, and the potential for common method bias. Suggestions for future research include conducting longitudinal studies, comparing across countries, adding variables such as job satisfaction and leadership style, and using a mixed methods approach for a deeper understanding of psychological and social factors.